FDG PET/CT Depicting Right Iliac Vein Tumor Thrombosis following Low Anterior Resection in Rectal Cancer Patient: A Case Report and Literature Review - Al-Ibraheem, Akram; Moghrabi, Serin (World Journal of Nuclear Medicine, 2023)
Venous tumor thrombus is a rare complication of rectal cancer but is more common in other types of cancer, like renal cell carcinoma and hepatocellular carcinoma. The usual site of tumor thrombus in rectal cancer patients is the inferior mesenteric vein (IMV), which is seldom seen in the common iliac vein, with only a few cases reported till now. We present a case of fluorodeoxyglucose (FDG) avid right iliac vein tumor thrombosis after low anterior resection in a patient with rectal cancer and review the literature.
Keywords: rectal cancer; tumor thrombus; FDG PET/CT; nuclear medicine